Optimalisasi Pembelajaran PAI di Era Digital Dengan Model Blended Learning Tingkat SMA - Resti Nurillah; Marsha Affifah Amani; Mila Amelia Putri (Advances In Education Journal, 2025)
This research aims to analyze literature reviews on optimizing Islamic Religious Education learning in the digital era using a blended learning model at the high school level.  Theme determination, searching, literature selection, analysis and interpretation, and dissemination of results are all components of a Systematic Literature Review (SLR). This study uses fourteen articles published in 2019–2024 from various sources. The research emphasis is on three aspects. The research results show that: 1) Development of the Islamic Religious Education curriculum, 2) The effectiveness of the blended learning model in Islamic Religious Education learning can improve learning outcomes, motivation and involve students in the learning process. 3) Optimizing Islamic Religious Education learning using a blended learning model at the high school level is an effective strategy for improving the quality of learning and preparing students to face global challenges.